Why are countries' asset portfolios exposed to nominal exchange rates?. (February 2021) - Adams, Jonathan J.; Barrett, Philip
Highlights: Observes that countries are exposed to exchange rate risks on their debt holdings. Shows that taking account of this can explain movements in consumption and exchange rates. Includes this mechanism in a standard international macroeconomic model. Motivates and applies a novel computational technique to solve the model. Abstract: Most countries hold large gross asset positions, lending in their domestic currency and borrowing in foreign currency. As a result, their balance sheets are exposed to nominal exchange rate movements. We argue that when asset markets are incomplete, this exposure provides partial insurance against shocks that move exchange rates. We demonstrate that this insurance motive can simultaneously generate realistic gross asset positions and resolve the Backus-Smith puzzle: that countries' relative consumption and real exchange rates are negatively correlated. Local perturbation methods are inaccurate in this setting as they approximate around the wrong interest rate, even when they correctly characterize the average portfolio holdings. So to accurately solve the equilibrium portfolio problem, we extend Maliar and Maliar (2015)'s global projection method.